Paying Attention: Focusing Your Congregation on What Matters - Peluso-Verdend, Gary, (Rowman & Littlefield Publishers, 2005)
In a culture marked by what many call “attention-deficit disorder,” congregations and their leaders are subject to distractions that detract from their mission and lead them in directions that have little to do with their reason for existence. Size concerns, building preservation, situational conflicts, the lure of technology, and the so-called worship wars all threaten to distract congregations from what matters most. Thus, churches can become part of the problem rather than a positive influence in the lives of their people and their communities. In this inspiring volume, Gary Peluso-Verdend issues a clarion call to congregational leaders to refocus their church’s attention on the core matters of Christian faith—the Word, the example of Christ, and an intentional embrace of theology and spiritual practice—to renew the congregation’s vision and to center itself again on God’s call. Paying Attention takes on obsession and anxiety, the two “vampires of attention,” that focus on the unfixable past and the uncontrollable future, wasting and dissipating attention. True Christian attention is focused on the now, and this book calls on congregations to be present to the persons and issues that God has entrusted to them. As Jesus of Nazareth’s ability to be fully attentive and present to people was remarkable, congregations should look to his example and attend as he attended. Paying Attention urges congregations to develop their theology of attention and to engage in the Christian practice of attending lovingly to God and to neighbor so that they may participate fully in the kingdom of God. With study questions at the end of each chapter and an imagined conversation between people practicing theology in their congregation, Paying Attention provides an invaluable companion in a congregation’s journey toward purposeful, attentive faithfulness.